The impact of 'playing victim' behavior on students' communication skills in chemistry learning - Azzajjad, Muhammad Fath; Ahmar, Dewi Satria (Arfak Chem: Chemistry Education Journal, 2025)
Students' communication skills can be influenced by “playing victim” behavior. No study explicitly links playing victim behavior with a decrease in student communication skills in chemistry learning, even though affective aspects such as this have great potential to influence interaction and understanding of scientific concepts collaboratively. This research aims to discover how such behavior impacts students' communication skills at SMAN 1 Sindue Tobata. This study used descriptive and inferential quantitative methods. As part of this study, 64 students from two Natural Science Program Batch 2023 classes were given questionnaires. The analysis showed that the p values for the victim group (p = 0.4194) and the non-victim group (p = 0.8846) were greater than alpha 0.05, indicating normal data distribution. In addition, the t-test showed a significant difference in communication skills between the two groups (t = -3.7365, p = 0.0004), with the victimized group showing lower communication skills. According to this study, students' communication skills in chemistry learning can be affected by “playing-victim” behavior.